2018
DOI: 10.1155/2018/2431023
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Clinical Trial Comparing Bucket Handle and Cartilage Tympanoplasty Techniques for the Reconstruction of Subtotal or Anterior Tympanic Membrane Perforation

Abstract: Objective The purpose of the study is to compare the clinical outcome of the two techniques of Bucket Handle Tympanoplasty and Cartilage Tympanoplasty in achieving success in graft survival as well as acceptable auditory results. 60 patients who suffered chronic otitis media with anterior perforation of the tympanic membrane were chosen. The patients were randomly assigned using Block Randomization Method of two groups including patients who underwent Bucket Handle Tympanoplasty (n = 30) or those that underwen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…On examining the full texts, 92 articles were assessed as unsuitable where COM was not the primary disease (7), tympanoplasty subtypes were not the primary intervention (11), the article was not published in English (5), the article did not contain long‐term hearing outcomes (68) or the presented data were too limited (1). Thirty‐nine studies 14‐52 reporting long‐term hearing outcomes and/or complications following middle ear interventions were included for synthesis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…On examining the full texts, 92 articles were assessed as unsuitable where COM was not the primary disease (7), tympanoplasty subtypes were not the primary intervention (11), the article was not published in English (5), the article did not contain long‐term hearing outcomes (68) or the presented data were too limited (1). Thirty‐nine studies 14‐52 reporting long‐term hearing outcomes and/or complications following middle ear interventions were included for synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…Mean preoperative and postoperative pure tone audiometry was reported in accordance with the inclusion criteria, and was therefore suitable for quantitative synthesis, in 21 studies 14,17,18,20,21,24,25,31,32,36‐39,42,45‐47,49‐52 . 10 of these studies 20,21,24,25,32,38,39,42,45,52 reported air‐bone gap (ABG) data in sufficient detail so that it could be categorized in to bins of ≤20 dB HL or ˃20 dB HL.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tympanoplasty using a temporalis fascia graft is a mainstay surgical approach for the management of tympanic membrane perforation due to chronic otitis media, where the aim is to create a dry and non-infected environment in the ear, repair the perforated membrane, eradicate infection, and restore hearing loss. 14 Although use of temporalis fascia in initial tympanoplasties has been associated with high surgical success rates (93–97 per cent), 5 post-operative outcomes are largely unpredictable given the structural composition of fascia temporalis, which exhibits irregular elastic fibres and fibrous connective tissue. 6 Thus, various types of graft materials (e.g.…”
Section: Introductionmentioning
confidence: 99%